The revocatory appeal against condemnatory and absolutory disciplinary decisions in the Colombian law - Riascos Gómez, Libardo Orlando (Universidad Nacional del Litoral, 2019)
The extraordinary appeal for revocation takes up the guidelines provided in the Administrative Code of 2011 and amends the parameters of the revocation provided in Law 1952 of 2019 for disciplinary decisions. This special appeal is structured (i) as an essential mechanism for the defense of the rights of people who have been condemned in a disciplinary process, (ii) or for those who have filed a disciplinary complaint and the decision is absolute or definitive archiving of the process. The appeal for revocation has a brief and summary procedure, causes for configuration, preclusive procedural terms and substantive decisions.